2015
DOI: 10.1007/s40094-014-0162-4
|View full text |Cite
|
Sign up to set email alerts
|

Low and high frequency instabilities in an explosion-generated-plasma and possibility of wave triplet

Abstract: An explosion-generated-plasma is explored for low and high frequency instabilities by taking into account the drift of all the plasma species together with the dust particles which are charged. The possibility of wave triplet is also discussed based on the solution of dispersion equation and synchronism conditions. High frequency instability (HFI) and low frequency instability (LFI) are found to occur in this system. LFI grows faster with the higher concentration of dust particles, whereas its growth rate goes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
4
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
2
4
1
Order By: Relevance
“…Hence, it can also be said that the wave propagating at higher speed evolves into an instability having larger growth rate. This is the similar result as obtained recently in a nonrelativistic EGP [33]. Consistent to Ref.…”
Section: Numerical Solution To Dispersion Equation and The Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Hence, it can also be said that the wave propagating at higher speed evolves into an instability having larger growth rate. This is the similar result as obtained recently in a nonrelativistic EGP [33]. Consistent to Ref.…”
Section: Numerical Solution To Dispersion Equation and The Resultssupporting
confidence: 93%
“…Consistent to Ref. 33, the present plasma also supports a propagating mode which has a constant velocity (Fig. 2).…”
Section: Numerical Solution To Dispersion Equation and The Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…It is found that in the previous studies, dust particles have been neglected by the researchers, which become important plasma species in the Hall thrusters due to the erosion of the wall of the chamber and sputtering [22,23]. In general, it is found that current carried by the highly mobile electrons plays the important role in dust charging, and as a result, the dust particles are negatively charged in the plasma [24][25][26][27][28][29]. The & Hitendra K. Malik hkmalik@hotmail.com negatively charged dust particles will hinder the movement of ions and, hence, alter the thrust and efficiency of the thruster.…”
Section: Introductionmentioning
confidence: 99%